Susceptibility Trends of Urinary Tract Infections Over a 15 Year Period on a University Campus. (4th October 2017) - Hoffmann, Wesley; Donnelley, Monica; Ferguson, Thomas
Abstract: Background: Acute uncomplicated cystitis (AUC) is one of the most common infections for which antimicrobials are prescribed. Despite IDSA AUC guideline recommendations, prescribing practices are varied throughout the US. Per IDSA recommendations, nitrofurantoin (NTF), fosfomycin, and trimethoprim/sulfamethoxazole (TMP/SMX) are all considered first line therapy for AUC, however there is concern of resistance to some of these agents. Quality improvement activity at the University of California, Davis Student Health Center (UCDSHC) has made prescribing NTF preferred for acute cystitis since 2001 as TMP/SMX has community resistance rates of 20%. Ciprofloxacin is the second line agent at UCDSHC. Methods: UCDSHC reviewed all urine cultures and susceptibilities for clinical and epidemiologic purposes. Susceptibility results were gathered from the UCDSHC microbiology laboratory from 2001–2016. Prescribing data was obtained from UCDSHC under diagnosis codes consistent with cystitis or UTI to demonstrate antibiotic prescribing trends. Susceptibilities were evaluated over the 15-year time period (2001–2016). TMP/SMX, FQ's, and NTF were the primary agents evaluated in this study. Results: From 2001–2016, 3, 831 E. coli and 296 S. saprophyticus isolates were evaluated, accounting for 88% of the total number of organisms. E. coli susceptibilities to NTF remained >98% from 2001–2016. E. coli susceptibilities to FQ's trended down from 99% in 2001 to 88% in 2016. E. coli susceptibilities to TMP/SMX remained stable around 80% from 2001–2016. S. saprophyticus remained highly susceptible to NTF, FQ's, and TMP/SMX (95%, 97%, and 100% respectively at the end of the study period). In total, 12, 298 prescriptions were written from 2008–20016. Eighty percent (9, 875) were NTF and 17% (2, 016) were FQ's. The remaining 1% and 2% were TMP/SMX and 'Other', respectively. Conclusion: After changes in prescribing practice in 2001, NTF was used in 80% of cystitis cases over 15 years and retained excellent activity against common urinary pathogens. FQ's retained acceptable activity for empiric use for urinary tract infections, but susceptibilities trended down notably despite limited FQ use. TMP/SMX did not regain increased activity over the time period. Disclosures: All authors: No reported disclosures.